Industrial Services Characterization for Bidding Process. Issue 13 (2019) - Guillon, D.; Villeneuve, E.; Merlo, C.; Vareilles, E.; Aldanondo, M.
Abstract: When responding to call for tenders, many bidding companies offer services. This paper focuses on how to model industrial services during the bidding process to be able to easily develop them. A product offer configuration model is presented, then a reflection about the extension of this model to service offers is conducted. A study of the literature about service definition is dealt and services characteristics are identified. Their impact on the product offer model is analyzed and new characteristics are introduced. This work makes possible to propose a typology to adapt the product offer model to services.